Differential expression of tumor necrosis factor α, interleukin 1β, nuclear factor κB in nasal mucosa among chronic rhinosinusitis patients with and without polyps - Plewka, Danuta; Grzanka, Alicja; Drzewiecka, Elzbieta; Plewka, Andrzej; Misiołek, Maciej; Lisowska, Grażyna; Rostkowska-Nadolska, Beata; Gawlik, Radoslaw (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: The pathogenesis of nasal polyps is still not fully understood. Aim : To analyze the topography and intensity of interleukin 1β (IL-1β), tumor necrosis factor α (TNF-α), cyclooxygenase 2 (COX-2), nitric oxide synthase 2 (NOS-2), and nuclear factor-κB (NF-κB) expressions in eosinophilic and neutrophilic polyps and in normal nasal mucosa. Material and methods : The study included specimens from 20 patients with eosinophilic polyps (more than 10% of eosinophils in inflammatory infiltrate), 20 individuals with neutrophilic polyps (predominance of neutrophils and less than 10% of eosinophils), and samples of normal nasal mucosa from 10 controls. The expressions of studied proteins in vascular endothelial cells, epithelial, stromal and glandular cells were determined immunohistochemically with specific monoclonal antibodies. Results : Irrespective of the cellular type, the intensity of expressions in eosinophilic and neutrophilic polyps was significantly higher than in the normal mucosa. Eosinophilic polyps were characterized by stronger expressions of TNF-α (in all cellular types), IL-1β (in endothelial, glandular and epithelial cells), NF-κB (in stromal and epithelial cells), COX-2 (in glandular and stromal cells), and NOS-2 (in endothelial and stromal cells). In contrast, neutrophilic polyps showed significantly stronger expressions of COX-2 (in epithelial and endothelial cells) and NOS-2 (in glandular and epithelial cells). In both phenotypes, the strongest expressions of all studied markers were documented in vascular endothelial cells. Conclusions : Inflammatory markers are involved in pathogenesis of both eosinophilic and neutrophilic polyps. Endothelial defects can play an important role in the development of nasal polyps.